2021
DOI: 10.4018/ijesma.2021010101
|View full text |Cite
|
Sign up to set email alerts
|

“Hey Alexa, Let's Shop”

Abstract: Millennials quickly adapt to new technologies and have been found to use voice technology daily. This study follows the technology acceptance model (TAM) developed by Davis to explain the relationships between perceived ease of use (PEOU), perceived usefulness (PU), perceived enjoyment (PE), and perceived innovativeness (PI) to behavioral intention (BI) for Millennials. An online survey generated 204 usable responses through Amazon Mechanical Turk. Multiple regression analyses supported the relationship of PEO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Supporting this, ref. [45,46] found that perceived usefulness, alongside perceived enjoyment and innovativeness, significantly impacts millennials' behavioral intention to use voice-activated shopping technologies. In parallel, perceived ease of use, another fundamental aspect of the TAM, signifies the extent to which a person believes that using a system will be effortfree [9].…”
Section: Proposed Model and Hypothesis Developmentmentioning
confidence: 99%
“…Supporting this, ref. [45,46] found that perceived usefulness, alongside perceived enjoyment and innovativeness, significantly impacts millennials' behavioral intention to use voice-activated shopping technologies. In parallel, perceived ease of use, another fundamental aspect of the TAM, signifies the extent to which a person believes that using a system will be effortfree [9].…”
Section: Proposed Model and Hypothesis Developmentmentioning
confidence: 99%